NAVIGATING THE DIGITAL DEMOCRACY: A MULTIDIMENSIONAL EXPLORATION OF THE RIGHT TO EXPRESS DISSENT ON SOCIAL MEDIA PLATFORMS IN THE AGE OF INFORMATIONAL ACTIVISM - Ligade, Pallavi; Menon, Hema (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today’s digital age, social media has transformed the way individuals communicate, share ideas, and engage in public debates. These platforms offer unprecedented access to information and serve as a space for discussion, activism, and advocacy. However, they also present challenges when it comes to expressing dissent, as digital communication operates within legal frameworks, corporate policies, and ethical boundaries.